Numerical Analysis of the Effect of Scanning Speed on the Temperature Field Distribution for Laser Heat Treatment Applications - Al-Najjar, Furat I. Hussein (Al-Nahrain Journal for Engineering Sciences, 2018)
One of the unique properties of laser heating applications is its powerful ability for precise pouring of energy on the needed regions in heat treatment applications. The rapid rise in temperature at the irradiated region produces a high temperature gradient, which contributes in phase metallurgical changes, inside the volume of the irradiated material. This article presents a comprehensive numerical work for a model based on experimentally laser heated AISI 1110 steel samples. The numerical investigation is based on the finite element method (FEM) taking in consideration the temperature dependent material properties to predict the temperature distribution within the irradiated material volume.  The finite element analysis (FEA) was carried out using the APDL scripting language (ANSYS Parametric Design Language) that is provided by the commercial code ANSYS. Infrared (IR) thermography technique was used to explore the workpiece surface and to validate the obtained results. The work takes into account the effect of different speeds of the laser beam and pulses overlap on the temperature pattern of the material surface and depth.